2008
DOI: 10.1111/j.1468-232x.2008.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Employers Give Discretion? Family Versus Performance Concerns

Abstract: Using a large data set of Western European employees, I examine two sets of reasons behind employers' decisions to give discretion: performance concerns (firms give discretion in order to improve performance) and family concerns (firms wish to improve the employees' work-family balance). I find more support for the former than for the latter. Discretion is positively related to the use of "high-performance" work practices and to employee position and ability, and is smaller in larger establishments, which sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 28 publications
5
89
0
1
Order By: Relevance
“…However, schedule control is not only used to address workers' family demands, but also to enhance performance (Ortega 2009). Schedule control can be used as a part of a high-involvement system (Wood and de Menezes 2010) or high-performance strategy, which believes that allowing workers more discretion and influence over their work can help improve performance (Davis and Kalleberg 2006).…”
Section: What Is Schedule Control?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, schedule control is not only used to address workers' family demands, but also to enhance performance (Ortega 2009). Schedule control can be used as a part of a high-involvement system (Wood and de Menezes 2010) or high-performance strategy, which believes that allowing workers more discretion and influence over their work can help improve performance (Davis and Kalleberg 2006).…”
Section: What Is Schedule Control?mentioning
confidence: 99%
“…Those in high-skill positions, more highly educated workers and workers at higher occupational levels are most likely to have access to schedule control (Golden 2009;Ortega 2009;Brescoll et al 2013). Workers in disadvantaged positionse.g.…”
Section: Who Has Access To Schedule Control?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ortega (2009) found that the use of discretionary FWAs was positively associated with "high-performance" work systems, and that employer motivations were more closely connected to organisational performance indicators (with employees identified as higher performing granted more discretion) than concerns for work-family balance.…”
Section: Established Themes In Flexible Work Researchmentioning
confidence: 99%
“…The literature emphasizes two motives for adopting some form of working-time autonomy [1]. First, similar to other decentralization policies, working-time autonomy could boost firm performance by improving worker motivation and by tapping into the superior knowledge of workers at lower levels of a firm's hierarchy.…”
Section: Performance Effects Of Working-time Autonomymentioning
confidence: 99%